26 Evaluation of sire versus dam effect on age at first calving in Brahman heifers. (30th November 2020) - Earnhardt, Audrey L; Neuendorff, Don A; Long, Charles R; Welsh, Thomas H; Randel, Ron D
Abstract: This study evaluated the possible effects of sire and dam on age at first calving in Brahman heifers. A total of 570 heifers born between the years 2001 and 2017 were exposed as yearlings to fertile bulls through time of pregnancy determination. A calving code was determined by calculating the mean (993 d) and standard deviation (187 d) of heifer age at first calving. Heifers considered to calve early (≤899 d; calving code = 1) or late (≥1087 d; calving code = 3) were at least half a standard deviation (94 d) away from the mean. All other heifers were considered to have a normal age at first calving (900 to 1086 d; calving code = 2). There were 35 sires with 5 or more daughters, resulting in a total of 543 heifers evaluated for the effect of sire. There were 323 daughters of evaluated heifers, which were evaluated for the effect of dam calving code. Also evaluated was the effect of dam and sire calving code on age at first calving of female offspring (n = 287). Variables analyzed included dam and sire of the heifer, age at first calving, and calving code. Data were analyzed using the GLM procedures of SAS and proportions were tested using Chi-square. Sire calving code did affect (P < 0.01) age at first calving and calving code in heifers, but dam calving code did not affect daughter calving code and age at first calving (Table 1). The proportion of daughters calving early compared to sire calving code significantly differed from the expected proportions (P < 0.01), whereas the proportions of daughters calving early for dam calving code did not differ (Table 2). A selection effort to produce Brahman heifers capable of calving early will not be effective from the dam side, but can be effective on the sire side.